An Analysis of Students’ Abilities in Mastering Vocabulary in Descriptive Texts at Pangeran Antasari Vocational School Medan - Nababan, Citrayani; Tampubolon, Jonris (English Lecturers and Teachers Association (ELTA), 2024)
This study aimed to find out the students’ vocabulary mastery in descriptive text and to know the challenges students face in mastering vocabulary in descriptive text in Pangeran Antasari Vocational School Medan. The research was conducted using a qualitative research approach using descriptive methods. The subjects of this study were first-grade students X-TB of Pangeran Antasari Vocational School Medan. Data collection techniques were carried out using vocabulary tests and interviews. The research results stated the number of students who achieved the KKM is 16 students with a percentage of 69,6% and under the KKM is 7 students with a percentage of 30,4%. It can be seen that on average students are able to exceed the Criteria Minimum Completeness (KKM) with an average score of 79, while the KKM for completion of English subjects that apply at Pangeran Antasari Vocational School Medan is 75. Keywords : Vocabulary Mastery: Descriptive Text